Elevated tumour markers in the pleural effusion of a patient with spontaneous esophageal rupture: a rare case report - Huaimin Liang; Xiaoning Li; Zhengliang Wei (Journal of Cardiothoracic Surgery)
Abstract Background Esophageal rupture is a rare but life-threatening condition. Esophageal tumours do not usually cause esophageal ruptures, and elevated tumour markers have rarely been detected in pleural effusion after esophageal rupture with no detectable tumour. The presence of elevated tumor markers in pleural effusion can lead to a misdiagnosis of esophageal cancer in patients with esophageal rupture, resulting in inappropriate treatment. Case presentation The 65-year-old male patient who was admitted to the emergency department with left chest pain and dyspnoea after severe vomiting. Chest computed tomography (CT) indicated left hydropneumothorax and mediastinal emphysema. The patient underwent bedside closed thoracic drainage. The drainage fluid was coffee-coloured and turbid, with significantly elevated CA199, CA125 and CEA levels. After transferring the patient to the emergency operating room, the esophageal defect was repaired, and a jejunostomy was performed. No tumours were detected in the thoracic cavity during surgery. The patient recovered and was discharged from the hospital. Conclusion Esophageal tumours should be suspected in patients with elevated pleural effusion CA199, CA125 and CEA levels. The findings from chest CT and oesophagography did not support the diagnosis of a thoracic tumor.These tumor markers may be concomitant changes during esophageal rupture.